Geopolitics at Home: Conflict, Civic Trust, and the Dynamics of Minority Religious Expression in Europe - Abbas, Tahir (The review of faith & international affairs, 2026)
This article examines religious identity among Christian, Jewish, and Muslim communities across four European nations. Survey data from 3,025 respondents reveal that societal threat heightens religiosity for minorities, although conditionally. Jewish respondents show increased religiosity linked to international conflict, whereas civic trust buffers this reaction among Muslims. These findings suggest religious intensification reflects social contexts rather than theological attributes. Consequently, cultivating civic trust is essential for social cohesion and mitigating defensive identification. The data demonstrate that local institutional relationships remain the primary determinants of minority identity expression within the secular state, offering a vital framework for policymakers addressing communal tensions.